Indian Economy - Vivek Singh (New Delhi, 2025)
The book serves as a comprehensive guide for candidates preparing for the UPSC Civil Services Examination, specifically focusing on GS Paper III's economic development section. It provides extensive coverage for both the preliminary and main stages of the exam. The content is designed to facilitate a deep understanding of the subject, blending static foundational concepts with contemporary issues. The book places a strong emphasis on the clarity of concepts, utilizing visual aids like diagrams, graphs, and flowcharts, along with numerous real-world examples to enhance comprehension. The material is thoughtfully updated with the latest economic data and government schemes. Valuable insights are offered through the inclusion of previous year UPSC Prelims and Mains Questions, aiding candidates in getting acquainted with the exam's pattern. To facilitate quick reference and comprehension, economic terms are compiled at the end of the book.
English
Keywords: Economics; Indian Economy